Waiting with Hope: How Waiting Time Shapes Patient Experience - Lulu Rahma Zahirah; Dwi Hurriyati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Waiting time for services is a crucial factor influencing patient satisfaction, especially in primary healthcare facilities such as community health centers. Patients who experience long waiting times tend to feel dissatisfied, both objectively and based on their perception of the service received. This study aims to analyze the relationship between waiting time and patient satisfaction at Tegal Binangun Community Health Center in Palembang and to identify which aspects of waiting time have the most significant impact on patient satisfaction. This research employs a quantitative correlational design, involving patients as respondents selected through purposive sampling. Data were collected using a questionnaire measuring waiting time aspects based on the theory of Herjunianto, Wardhani, and Prihastuty (2014) and patient satisfaction aspects based on the theory of Purwanto (2007). The findings indicate a significant negative correlation between waiting time and patient satisfaction (r = -0.590, p < 0.05), with a contribution of 34.8%. The aspects of Actual Waiting Time and Perceived Waiting Time show a stronger influence on patient satisfaction dimensions such as Reliability, Responsiveness, and Empathy. These results suggest that the longer the waiting time, the lower the level of patient satisfaction, highlighting the need for community health centers to improve service efficiency to reduce waiting times. The implications of this study emphasize the importance of optimizing queue management systems and enhancing communication between healthcare providers and patients to improve the overall healthcare experience in primary care facilities.Waktu tunggu pelayanan menjadi faktor penting yang memengaruhi kepuasan pasien, terutama dalam layanan kesehatan primer seperti puskesmas. Pasien yang mengalami waktu tunggu lama cenderung merasa tidak puas, baik secara objektif maupun berdasarkan persepsi mereka terhadap layanan yang diterima. Penelitian ini bertujuan untuk menganalisis hubungan antara waiting time dengan kepuasan pasien di Puskesmas Tegal Binangun Palembang serta mengidentifikasi aspek waiting time yang paling berpengaruh terhadap kepuasan pasien. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional, melibatkan pasien puskesmas sebagai responden yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui kuesioner yang mengukur aspek waiting time berdasarkan teori Herjunianto, Wardhani, dan Prihastuty (2014) serta aspek kepuasan pasien berdasarkan teori Purwanto (2007). Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara waiting time dengan kepuasan pasien (r = -0.590, p < 0.05), dengan kontribusi sebesar 34.8%. Aspek Actual Waiting Time dan Perceived Waiting Time memiliki pengaruh yang lebih kuat terhadap dimensi kepuasan pasien seperti Reliability, Responsiveness, dan Empathy. Temuan ini mengindikasikan bahwa semakin lama waktu tunggu, semakin rendah tingkat kepuasan pasien, sehingga penting bagi puskesmas untuk meningkatkan efisiensi pelayanan guna mengurangi waktu tunggu. Implikasi penelitian ini menegaskan perlunya optimalisasi sistem antrean dan peningkatan komunikasi antara tenaga medis dan pasien untuk meningkatkan pengalaman layanan kesehatan di fasilitas primer.